2011
DOI: 10.1371/journal.pgen.1002387
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast Stress-Responsive MAPK Pathway Promotes Meiosis via the Phosphorylation of Pol II CTD in Response to Environmental and Feedback Cues

Abstract: The RRM-type RNA-binding protein Mei2 is a master regulator of meiosis in fission yeast, in which it stabilizes meiosis-specific mRNAs by blocking their destruction. Artificial activation of Mei2 can provoke the entire meiotic process, and it is suspected that Mei2 may do more than the stabilization of meiosis-specific mRNAs. In our current study using a new screening system, we show that Mei2 genetically interacts with subunits of CTDK-I, which phosphorylates serine-2 residues on the C-terminal domain of RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…The latter scenario applies to the Ser2 coding letter, insofar as a heterothallic haploid fission yeast rpb1-S2A mutant can grow vegetatively, but is unable to mate with heterothallic WT cells of either mating type, i.e., S2A is sterile. Sterility results from the inability of S2A cells to induce expression of the Ste11 transcription factor that triggers the meiotic sexual differentiation pathway (5,6,8). Microarray analyses of the transcriptome of S2A cells vs. WT highlighted ≥1.5-fold changes in the expression level of many meiotically regulated genes (5,9).…”
Section: Significancementioning
confidence: 99%
“…The latter scenario applies to the Ser2 coding letter, insofar as a heterothallic haploid fission yeast rpb1-S2A mutant can grow vegetatively, but is unable to mate with heterothallic WT cells of either mating type, i.e., S2A is sterile. Sterility results from the inability of S2A cells to induce expression of the Ste11 transcription factor that triggers the meiotic sexual differentiation pathway (5,6,8). Microarray analyses of the transcriptome of S2A cells vs. WT highlighted ≥1.5-fold changes in the expression level of many meiotically regulated genes (5,9).…”
Section: Significancementioning
confidence: 99%
“…They include the cyclic adenosine monophosphate (cAMP) pathway, the target of rapamycin (TOR) complex 1 (TORC1) pathway and the two mitogen-activated protein kinase (MAPK) pathways (Yamamoto et al, 1997;Otsubo and Yamamoto, 2010). Recently, it has become apparent that phosphorylation of the C-terminal domain (CTD) of RNA polymerase II (Pol II) by CTD kinase I (Ctdk1) specifically affects the expression of ste11 (Coudreuse et al, 2010;Sukegawa et al, 2011). It has also been shown that the meiotic regulator Mei2, the expression of which is governed by Ste11, enhances expression of ste11 through a positivefeedback loop (Sukegawa et al, 2011).…”
mentioning
confidence: 99%
“…Recently, it has become apparent that phosphorylation of the C-terminal domain (CTD) of RNA polymerase II (Pol II) by CTD kinase I (Ctdk1) specifically affects the expression of ste11 (Coudreuse et al, 2010;Sukegawa et al, 2011). It has also been shown that the meiotic regulator Mei2, the expression of which is governed by Ste11, enhances expression of ste11 through a positivefeedback loop (Sukegawa et al, 2011). These new discoveries, together with previous findings, illustrate that a number of signal transduction pathways orchestrate the regulation of ste11 expression in response to intricate environmental changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations